Efficient and convenient synthesis, characterization, and antimicrobial evaluation of some new tetracyclic 1, 4-benzothiazines. Issue 2 (17th January 2016) - Mor, Satbir; Nagoria, Savita
ABSTRACT: In the present study, 20 new tetracyclic 1, 4-benzothiazines (4a –4 t ) were conveniently synthesized in good yields and characterized by different spectral and physical techniques. The in vitro antimicrobial evaluation of the synthesized benzothiazine derivatives was performed by serial dilution against two Gram-positive bacteria [ Bacillus subtilis (MTCC 441) and Staphylococcus epidermidis (MTCC 6880)], two Gram-negative bacteria [ Escherichia coli (MTCC 1652) and Pseudomonas aeruginosa (MTCC 424)], and two fungal strains [ Candida albicans (MTCC 227) and Aspergillus niger (MTCC 8189)]. The derivatives4 l and4 t were found to be more potent than standard drug, i.e., fluconazole, against A. niger and C. albicans, respectively. GRAPHICAL ABSTRACT: